Bevacizumab plus irinotecan in treatment of recurrent brain gliomas - Stec, Rafał; Bodnar, Lubomir; Smoter, Marta; Szczylik, Cezary (Contemporary Oncology/Współczesna Onkologia, 2010)
Malignant gliomas including WHO grade III and grade IV tumours are a rare neoplasm (0.5% to 1% of all cancers). No standard therapy is available in the case of disease recurrence. In this review we assess the available literature evaluating the effect of chemoimmunotherapy based on bevacizumab and irinotecan in patients with recurrent WHO grade III and IV gliomas. Malignant gliomas are highly vascular and often express abundant amounts of vascular endothelial growth factor (VEGF). Neoplastic progression is dependent on angiogenesis, and anti-VEGF therapy has been successful in multiple disease states. Bevacizumab is a humanized monoclonal antibody that binds to and inhibits the activity of VEGF. Bevacizumab combined with irinotecan, an inhibitor of topoisomerase I, with good penetration to the CNS, appears to improve 6-month progression-free survival by 29% to 55%. Conclusion: Bevacizumab in combination with irinotecan could be an active regimen for patients with recurrent WHO grade III and grade IV gliomas.